2003
DOI: 10.5507/bp.2003.023
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin concentrations as a criterion of metabolic control in persons with type 2 diabetes mellitus?

Abstract: 1) Do persons with type 2 diabetes have lower ADP values than individuals without DM but with a high risk of ATS complications? 2) Do ADP values differ between persons with well controlled and persons with uncontrolled type 2 diabetes? We examined 109 patients of the Metabolic Center of Hospital Sternberk. Out of them, 58 had type 2 diabetes, others were individuals with variously expressed risk factors of early atherosclerosis (obesity, hypertension, age, family history, smoking, dyslipidemia, etc.). In all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
1
10
1
3
Order By: Relevance
“…In the postmenopausal group, MBP was signi cantly, positively and independently correlated with TG, while a correlation was no longer observed between the MBP and adiponectin/BMI Discussion e present study showed a signi cant and independent inverse correlation between adiponectin/BMI and MBP in premenopausal, but not postmenopausal, women. While the present study also showed a signi cant and independent correlation between adiponectin/BMI and TG (inverse) and HDLcholesterol (positive), these results were consistent with a previous study [25]. e nding of a signi cant inverse correlation between adiponectin/BMI and MBP only in premenopausal women suggests that menopause can a ect the adiponectin-BP relationship; namely, premenopause may be a relatively speci c condition during which this relationship exists.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In the postmenopausal group, MBP was signi cantly, positively and independently correlated with TG, while a correlation was no longer observed between the MBP and adiponectin/BMI Discussion e present study showed a signi cant and independent inverse correlation between adiponectin/BMI and MBP in premenopausal, but not postmenopausal, women. While the present study also showed a signi cant and independent correlation between adiponectin/BMI and TG (inverse) and HDLcholesterol (positive), these results were consistent with a previous study [25]. e nding of a signi cant inverse correlation between adiponectin/BMI and MBP only in premenopausal women suggests that menopause can a ect the adiponectin-BP relationship; namely, premenopause may be a relatively speci c condition during which this relationship exists.…”
Section: Resultssupporting
confidence: 81%
“…e objective of the present study was to investigate the relationship between adiponectin and BP in premenopausal and postmenopausal women. Considering that adiponectin is derived speci cally from adipose tissue, the level of BMIadjusted adiponectin (adiponectin/BMI) was used as a measure of adiponectin in this study, as reported previously [25][26][27].…”
mentioning
confidence: 99%
“…Dyslipidaemia is a metabolic syndrome risk factor identified by (a) high circulating TAG or (b) a low level of HDL cholesterol (table 1). Similar to obesity and insulin resistance, numerous studies have shown that dyslipidaemia is associated with low circulating adiponectin even in the absence of other metabolic syndrome risk factors [36,89,[108][109][110][111][112][113][114][115][116][117][118][119][120]. The possibility that low adiponectin levels may trigger dyslipidaemia is corroborated by the link between the G276G polymorphism (intron 2) compared with the G/T and T/T genotypes [121].…”
Section: Dyslipidaemia and Adiponectinmentioning
confidence: 99%
“…Resistin, leptin ve ObRe ile adiponektin arasında belirgin ilişki saptanmamıştır. Çalışmayı yürütenler sonuç olarak; tip 2 diyabetik hastaların diğer yük-sek aterosklerotik risk taşıyan popülasyondan daha düşük serum adiponektin seviyelerine sahip olduğu, iyi glisemik kontrol yapılan hastaların daha yüksek serum adiponektin düzeyine sahip olduğu ve adiponektinin metabolik kontrol ve aterosklerotik risk açısından iyi bir belirteç olduğunu değerlendirmişlerdir [15]. Okamoto ve ark.…”
Section: Discussionunclassified
“…Epidemiyolojik çalışmalarda insülin direncinin KVH risk faktörü olduğu ortaya konulmuştur. İnsülin direnci; dislipidemi, obezite, diyabet ve hipertansiyon ile ilişkilidir [15]. Hipertansiyona %30-50 insülin direncinin eşlik ettiği bildirilmiştir ve birçok çalışmada kan basıncı ile açlık plazma insülin arasındaki anlamlı ilişki gösterilmiştir.…”
Section: Discussionunclassified